COVID-19 Crisis: Challenges to Human Resource Management (HRM) - Gonawan, Siti Aisyah; Othman, Siti Amira (Journal of Techno-Social, 2022)
The pandemic COVID-19 crisis have affected globally in every areas of economic businesses as well as the management of human resource in organization. This studies aims to explore in the challenges faced by Human Resource Management (HRM) functions during the COVID-19 crisis. The method used for this study is by reviewing literature of previous study by exploring how COVID -19 impacted HRM and how HRM cope with the situation. It is revealed that the pandemic COVID -19 crisis have impacted and give challenges to the HRM function in an organization. In conclusion, the challenges arise from these pandemic has disrupted human resource strategies in managing the workforce.